Study on the influence of droplet agglomeration on the removal of aerosol by spray system. (October 2021) - Yu, Huiyu; Gu, Haifeng; Sun, Zhongning; Zhou, Yanmin; Sun, Chaojie; Chen, Junyan; Li, Yingzhi
Abstract: Aerosol is an essential class of radioactive source term in containment under severe accidents. The potential leak of aerosol into the environment will cause catastrophic radioactive pollution. Hence, it is significant to study the measures of aerosol removal in containment. One of the most efficient and widely used methods of removing aerosols is the sprinkle of the droplet. The current numerical research presented a model for predicting the evolution of the aerosol with the spray system activation. The present model includes the agglomeration of spray droplets. Polydisperse droplets and polydisperse aerosol particles are employed in the simulation. The data of the COSTTHES experiment is utilized to validate the numerical model. The model analyses indicate that the removal constant of aerosol is determined by the flow rate distribution of the droplet size group and the spray parameter ( ε / D ) . The influence of droplet agglomeration on aerosol removal isn't monotonic. It is decided by the specific size distribution of the droplet and the distribution of the spray parameter ( ε / D ) .